Africa in world agricultural trade: Recent trends and carbon footprint - Odjo, Sunday; Berthe, Abdrahmane; Diallo, Mouhamadou Hady (AKADEMIYA2063, 2024)
Agriculture, deeply embedded within the cultural and economic fabric of African societies, is a linchpin for the continent’s socioeconomic advancement. With its diverse array of climatic conditions, Africa hosts a spectrum of agricultural practices, ranging from traditional subsistence farming to modern commercial enterprises. However, alongside agriculture’s pivotal role in livelihoods and economic growth, the sector poses a challenge as a significant contributor to greenhouse gas (GHG) emissions. Against this backdrop, a nuanced understanding of the intricate relationship among agricultural activities, emissions, and international trade emerges as crucial for balancing sustainable development within Africa and global climate change mitigation efforts. In an era marked by the urgent imperative to address climate change and curb GHG emissions, the role of agriculture has come under intense scrutiny (Smith et al. 2014). The global agriculture sector, intricately interwoven with international trade, underscores the multifaceted environmental complexities inherent in agricultural production and distribution. Climate change significantly impacts global agrifood trade dynamics, influencing production patterns, market accessibility, and economic resilience (Bozzola, Lamonaca, and Santeramo 2023; Gouel and Laborde 2021; Lamonaca, Bozzola, and Santeramo 2024). These effects are compounded by climate-induced shifts in crop yields, water availability, and temperature regimes, altering both supply and demand dynamics across international markets. Notably, agricultural goods traded across borders “carry” the emissions generated during their production and transportation. This notion of emissions embodied in exports and imports has garnered increasing attention in contemporary literature (Davis and Caldeira 2010). Recent studies emphasize the significant interlinkages between climate change and emissions embedded in trade within the agrifood sector. For example, Santeramo, Ferrari, and Toteti (2024) explore the intricate balance required to achieve climate change and environmental goals without resorting to protectionist measures, emphasizing the complexities of international trade policies in mitigating emissions. Li et al. (2023) highlight that despite efficiency gains along global supply chains, changes in global food consumption patterns have contributed to increased GHG emissions, underscoring the need for sustainable trade practices to mitigate environmental impacts.